Adequacy Analysis of Green Open Space and its Development Direction as an Attributes of Green City in the Capital of Jember Regency, Indonesia - Sitorus, Santun R.P.; Wardani, Imelda Kusuma; Mulya, Setyardi Pratika (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
The development of an urban area needs to pay attention to the environmental carrying capacity. One of the way to achieve sustainable urban development is to apply one of the attributes of green city namely green open space (GOS). The purpose of the research are to analyze the types of land use in the years of 2010 and 2017, to analysis land use changes from 2010 to 2017, predicting land use change, analyzing the adequacy of GOS by area acreage and population number, and to determine the direction of GOS development in the Jember City.The research was conducted in the Capital of Jember Regency, namely Jember City with the total area of 9,900 ha. Methods of data analysis are the spatial analysis, analysis of population growth with quadratic growth model, Cellular Automata-Markov, and synthesis of green open space (GOS) development direction based on potential land and the value of the land. The results showed that there are ten types of land use in the Jember City, those are forest, mixed gardens, dryland agriculture, open land, cemetery, plantation, settlements and buildings, paddy fields, shrubs and grasses, and river. A relatively large land use changed in the period of 2010-2017 were dryland agriculture and paddy fields into settlements and buildings. The results of land use prediction with Cellular Automata-Markov described the trend of land use change becomes settlements (buildings) and plantations. The adequacy of public GOS by area as well as population still lacking whereas the adequacy of private GOS has been exceeded. The GOS acreage based on number of population is lower than those GOS based on an area. The GOS development planning is required to fulfill the needs. The consideration used to draw up the directives is the existing land use, regional spatial plan (RTRW), prediction of land use in the year of 2024, distribution of GOS, and land values. Development plans of GOS consist of two stages namely stage 1 and stage 2 with three priorities, namely priority 1, priority 2, and priority 3 with the total area 1,052 ha and funding require approximately two trillion rupiahs. The acreage of potential land for development of GOS has already enough to fulfill the needs of GOS based on population, however, not yet sufficient to fulfill the needs of GOS based on regency area.